Elements of State and Federal Prison Suicide Prevention and Response Policies - Tartaro, Christine (Criminal justice policy review, 2024)
There are no mandatory national standards for custodial suicide prevention and response programs in the United States. While some professional organizations do offer accreditation, those programs are optional. Recent research on jails found that most facilities have formal suicide prevention policies, but they differ in their comprehensiveness. Little is known about the elements of state and federal prison suicide prevention policies. This study involves an analysis of state- and federal-level department of corrections suicide prevention and response policies. Elements of each jurisdiction’s policies were compared against a list of best practices, developed by professional organizations and correctional suicide scholars, for suicide prevention and response. Results revealed that, on average, department policies contain about half of the recommended elements, and that some policies, including those that could improve the culture of each institution, are not included in most departmental policy documents.